The Effect of Funding Decisions, Dividend Policy and Profitability on Firm Value with Good Corporate Governance as a Moderating Variable - Haniah, Titi Hidayati Helmasari; Solihin, Solihin; Singawinata, Indra Pradana (JASa (Jurnal Akuntansi, Audit dan Sistem Informasi Akuntansi), 2024)
Businesses involved in real estate and property that have been listed on the Indonesia Stock Exchange between 2016 and 2023 will be the focus of this research. It will examine the relationship between business value and GCG, as well as the effects of funding decisions, dividend policy, and profitability. The method used in this research is quantitative method. A total of fifteen businesses served as the sample. Purposive sampling with path analysis using Smart PLS version 3 tools is the methodology adopted. Firm value is favorably and considerably affected by funding decisions, dividend policy, profitability, and GCG, according to this study. While dividend policy and profitability have a stronger influence on firm value, funding decisions have less of an effect when GCG is effective. Firms in the property and real estate industry would do well to prioritize raising profits if they want to increase their firm worth, according to the results of this study. Additionally, improving GCG practices is crucial for fostering long-term growth and advancing the company, ultimately yielding greater benefits in the future.